The Effect of Transformational Leadership and Interpersonal Communication on Guru Penggerak Work Effectiveness: The Mediating Role of Learning Organization and Work Motivation (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to examine the direct and indirect effects of transformational leadership and interpersonal communication on the work effectiveness of Guru Penggerak in curriculum implementation, with learning organization and work motivation as mediating variables. Methods: A quantitative survey design was employed involving 116 Guru Penggerak teachers from public elementary schools in Bogor Regency, selected through proportional random sampling. Data were collected using validated questionnaires and analyzed using descriptive statistics, prerequisite tests (normality, homogeneity, and linearity), and path analysis supported by the Sobel test to examine mediation effects. Results: The findings indicate that transformational leadership, interpersonal communication, learning organization, and work motivation have positive and significant direct effects on teacher work effectiveness. Learning organization and work motivation are the strongest predictors. Additionally, both variables significantly mediate the relationship between leadership, communication, and work effectiveness, with indirect effects found to be stronger than direct effects. Novelty: This study offers an integrative causal model that combines leadership, communication, organizational learning, and motivation in explaining teacher work effectiveness. It also highlights the dominant mediating role of learning organization and work motivation, providing a more comprehensive understanding of how leadership and communication influence educational outcomes in the context of curriculum reform.